English legal history and its sources essays in honour of Sir John Baker - Ibbetson, David J.; Jones, Neil; Ramsay, Nigel 1955- (Cambridge University Press, 2019)
"This volume honours the work and writings of Professor Sir John Baker over the past fifty years, presenting a collection of essays by leading scholars on topics relating to the sources of English legal history, the study of which Sir John has so much advanced. The essays range from the twelfth century to the nineteenth, considering courts (central and local), the professions (both common law and civilian), legal doctrine, learning, practice, and language, and the cataloguing of legal manuscripts. The sources addressed include court records, reports of litigation (in print and in manuscript), abridgements, fee books and accounts, conveyances and legal images. The volume advances understanding of the history of the common law and its sources, and by bringing together essays on a range of topics, approaches and periods, underlines the richness of material available for the study of the history of English law and indicates avenues for future research"...
Keywords: Geschichte; HISTORY / Europe / Great Britain / bisacsh; Law -- Great Britain -- History; HISTORY / Europe / Great Britain; Recht; Großbritannien; Festschrift